Kemampuan Petani dalam Usahatani Padi Sawah di Desa Ronta, Kecamatan Bonegunu, Kabupaten Buton Utara - Monalisa, Monalisa; Hamzah, Awaluddin; Suriana, Suriana (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2023)
The research is motivated by the production which is still low at 1.1 tons/ha, of course it is still far from the national average rice production which is around 5.7 tons/ha. One of causes of the decline in rice production is the ability of farmers to improve. This study aims to determine the ability of farmers in lowland rice farming, both in the form of farmer knowledge and farmer skill in the farming process, starting from land processing, planting, fertilizing, irrigation, and harvesting. The sampel in this study was determined throught of census method. The number respondent of rice farmers as many as 14 farmers. Analysis of the data used this study is a quantitative descriptive method that is processed with the class interval formula. The result of thus study indicate that farmers in ronta village, bonegunu district, north buton regency are in the capable category, it can be seen trought the knowledge and skill of farmers.